Analisis Komunikasi Antarpribadi dalam Hubungan Pasangan Jarak Jauh Berbasis Media Digital - Bunga Febrian; Defina Palupi Kurniasari; Nur Amanah Billa; Nafila Adinda Rini; Mila Yunita (SENTRI: Jurnal Riset Ilmiah, 2026)
This study examines the dynamics of interpersonal communication in long-distance relationships conducted through digital media. The study uses a descriptive qualitative approach with data collection through in-depth interviews with four informants aged 20–23 years who are in long-distance relationships. Data analysis was conducted using Miles and Huberman's interactive model to identify communication patterns relevant to DeVito's six aspects of communication, namely self-disclosure, empathy, emotional support, feedback, emotional involvement, and conflict management. The results showed that digital media served as a space to bring emotional presence, maintain psychological attachment, and reduce potential misunderstandings through communication style adjustments. Respondents with more active media usage showed greater self-disclosure, the ability to read emotional cues digitally, and more responsive feedback patterns. Meanwhile, the limitations of direct interaction required couples to be more careful in managing conflict and choosing the right time to communicate. Overall, this study confirms that the quality of interaction through digital media plays an important role in maintaining the stability and intimacy of long-distance relationships.